Organizational commitment of health professionals and associated factors in primary healthcare facilities of Addis Ababa, Ethiopia: A multi-center cross-sectional study - Arage, Sulyeman Mohammed; Daba, Derese Bekele; Dessalegn, Abere Yekoye (Frontiers in Public Health, 2022)
Background Organizational commitment has a positive impact on an organization's ability to provide professional services. Committed human power pushes an organization to achieve its goals, but non-commitment can lead to increased medical errors, prolonged inpatient admissions, and repeated hospitalizations leading to low quality of healthcare provision. However, to the best knowledge of researchers, there are no studies examining organizational commitment in the healthcare setting of Addis Ababa, Ethiopia. Objective The aim of this study was to assess the level of organizational commitment and associated factors among health professionals working in the primary health facility of Addis Ababa, Ethiopia. Methods A facility-based cross-sectional study was conducted among 459 healthcare professionals selected by simple random sampling from 12 health centers. Data were collected by three data collectors and one supervisor using a pretested questionnaire. Data were checked for completeness, cleaned, and entered into Epi-Data version 3.1.and exported into SPSS version 25 for analysis. In binary logistic regression statistical analysis, variables with p < 0.2 were entered in multivariate binary logistic regression analyses; then, the regression result was presented using COR, AOR with 95% CI, and a p-value < 0.05 as a level of significance. Result The respondent's percent mean score of organizational commitment was 48.4%. Age group above 30 years (AOR = 1.52, 95% CI, 1.01, 2.30), those who were satisfied with their job (AOR 2.02, 95% CI 1.30, 3.13), and those who perceive good transformational leadership behavior (AOR: 1.85, 95% C.I, 1.18, 2.90) were significant factors of organizational commitment among health professionals. Conclusion and recommendation Organizational commitment was lower in magnitude in the study setting. Age, job satisfaction, and transformational leadership behavior were significant predictors of organizational commitment.